Time Poverty among Working Females in Pakistan: A Qualitative Study - Iqbal, Fatima; Ahmad, Muhammad Bilal; Hussain, Rai Imtiaz; Aslam, Sohail; Ali, Hafiz Fawad (International Journal of Economics and Financial Issues, 2020)
Time is a scarce resource. Females in Pakistan are considered to be time poor since they are burdened with paid as well as non-paid work. Recent labor force statistics reveal female workforce participation is not increasing as it should be and ‘being time poor’ is one of the many reasons. The current study sheds light on factors that make females time poor which has lead to decreased labor force participation. The study is qualitative in nature 15 respondents were interviewed which lead to identification of 7 major themes which include job timings higher studies, lack of support, societal pressure, child care, domestic responsibilities and patriarchal beliefs. Government must assist females in provisions of day cares, flexible job timings, awareness programs and female job quotas so that their participation in the labor force can be increased. Keywords: Time poverty, labor force participation, patriarchal society JEL Classification: I32, J21 DOI: https://doi.org/10.32479/ijefi.10251